Genetics, 3rd.ed - W., Strickberger Monroe ([S.l.] : Old Price, 1995)
Genetics occupies a unique central position among the various biological sciences because of its diverse specializations. This acclaimed book provides the basic theoretical information on genetics, the study of heredity and details some of the experiments and reasoning which yield this information. The book is organized into six parts and deals with the identification, transmission and distribution, arrangement, structure, and function of genetic material. The last part of the book deliberates on the course of genetic material in populations. The comprehensive material is supported by a multitude of illustrations and references and problems in every chapter. Table of contents preface. Acknowledgements part i? identification of genetic material: history of the problem. Cellular division and chromosomes. Reproductive cycles. Nucleic acids. Replication and synthesis of nucleic acids. Part ii?transmission and distribution of genetic material: mendelian principles: i. Segregation mendelian principles: ii. Independent assortment. Probability and statistical testing. Dominance relations and multiple alleles in diploid organisms. Environmental effects and gene expression. Gene interaction and lethality. Sex determination and sex linkage in diploids. Maternal effects and cytoplasmic heredity. Quantitative inheritance. Analysis of quantitative characters. Part iii?arrangement of genetic material: linkage and recombination. Gene mapping in diploids. Recombination in fungi. Recombination in bacteria. Recombination in viruses. Part iv?change and structure of genetic material: chromosome variation in numbe.
Keywords: genetics